Imaging biomarkers of TERT or GABPB1 silencing in TERT-positive glioblastoma. Issue 11 (23rd April 2022) - Minami, Noriaki; Hong, Donghyun; Stevers, Nicholas; Barger, Carter J; Radoul, Marina; Hong, Chibo; Chen, Lee; Kim, Yaewon; Batsios, Georgios; Gillespie, Anne Marie; Pieper, Russel O; Costello, Joseph F; et al.
Abstract: Background: TERT promoter mutations are observed in 80% of wild-type IDH glioblastoma (GBM). Moreover, the upstream TERT transcription factor GABPB1 was recently identified as a cancer-specific therapeutic target for tumors harboring a TERT promoter mutation. In that context, noninvasive imaging biomarkers are needed for the detection of TERT modulation. Methods: Multiple GBM models were investigated as cells and in vivo tumors and the impact of TERT silencing, either directly or by targeting GABPB1, was determined using 1 H and hyperpolarized 13 C magnetic resonance spectroscopy (MRS). Changes in associated metabolic enzymes were also investigated. Results: 1 H-MRS revealed that lactate and glutathione (GSH) were the most significantly altered metabolites when either TERT or GABPB1 was silenced, and lactate and GSH levels were correlated with cellular TERT expression. Consistent with the drop in lactate, 13 C-MRS showed that hyperpolarized [1- 13 C]lactate production from [1- 13 C]pyruvate was also reduced when TERT was silenced. Mechanistically, the reduction in GSH was associated with a reduction in pentose phosphate pathway flux, reduced activity of glucose-6-phosphate dehydrogenase, and reduced NADPH. The drop in lactate and hyperpolarized lactate were associated with reductions in glycolytic flux, NADH, and expression/activity of GLUT1, monocarboxylate transporters, and lactate dehydrogenase A. Conclusions: Our study indicates that MRS-detectable GSH, lactate, and lactate production could serve as metabolic biomarkers of response to emerging TERT-targeted therapies for GBM with activating TERT promoter mutations. Importantly these biomarkers are readily translatable to the clinic, and thus could ultimately improve GBM patient management.